Ecotoxicity assessment of dicationic versus monocationic ionic liquids as a more environmentally friendly alternative - Montalbán, M.G.; Villora, G.; Licence, P. (Elsevier, 2018)
One of the reasons why ionic liquids have received growing interest from researchers is their environmentally interesting characteristics, such as their negligible vapour pressure and their good chemical and thermal properties. In particular, dicationic ionic liquids whose thermal and electrochemical stability is higher than that of monocationic ionic liquids have begun to gain attention during recent years. In this work, monocationic and dicationic ionic liquids were synthesized, characterized and tested for their toxicity, which was assessed using the luminescent bacterium Vibrio fischeri. The results revealed that the toxicity of the ionic liquids mainly depends on the head groups and linkage chain length of their cationic structure. Introduction of a new cationic head decreased the EC50 (concentration which leads to 50% reduction in bioluminescence of the bacteria) of the ionic liquids. The results present a promising picture of dicationic ionic liquids as alternatives with lower environmental impact than their monocationic counterparts and underline the significance of designing particular structures for ionic liquids.